DIMENSIONALITY ANALYSIS OF MAGNETOTELLURIC DATA OF KUSATSU-SHIRANE VOLCANO, JAPAN - Muhamad Ferdi Julkarnain, Raden
The Magnetotelluric (MT) method is a passive electromagnetic (EM) method that involves measuring changes in the electric field E and magnetic field H originating from nature perpendicular to the earth's surface as a means to determine the structure of the earth's conductivity. The MT method has advantages over other geophysical methods. It has a high depth of penetration of the electromagnetic field, does not require additional or artificial generators, and has a small impact on the environment. With these advantages, the MT method can be used for exploration such as geothermal and research on volcanoes. However, volcanic areas usually have complex structures, namely 3-D structures. If 1-D or 2-D modeling is carried out directly without dimensionality analysis, the effects of 3-D structures will influence the results. Therefore, dimensionality analysis is needed so that modeling can be carried out where 3-D effects can be minimized. This research aims to determine the subsurface structure of Kusatsu Volcano, which can be known through dimensionality analysis of MT data, and to determine the strike direction through the theta swift value and the tipper. The results obtained from the phase tensor and tipper analysis show that the structure of Kusatsu volcano is dominated by 2-D or 3-D structures which indicates the presence of two conductive anomalies that occur at frequencies of 5200 Hz to 66 Hz, and there is only one conductive anomaly that appears at frequencies of 66 to 13,7 Hz. Based on tetha swift value, the strike direction is pointing to N100E or N200W at 5200 Hz, pointing to N100E or N100W at 320 Hz, pointing to N00E or N40W at 66 Hz, pointing to N00E or N50W at 13,7 Hz, and leads to N00E or N140W at a frequency of 1,41 Hz. From the skewness and ellipticity values, the subsurface structure of the Kusatsu-Shirane Volcano is also dominated by 3-D structures.